Optimised adaptive power on‐demand routing protocol for mobile ad hoc wireless network. Issue 4 (1st December 2014) - Bello, Lawal; Bakalis, Panos; Rapajic, Predrag; Anang, Kwashie A.
Abstract : A technique is developed for ad hoc on‐demand routing protocol. The protocol is based on the conventional on‐demand ad hoc routing protocols with the addition of power model. The algorithm design and development is aimed to incorporate the transmitted power consumption function in such a manner that mobile nodes are able to evaluate their power status to decide if they are fit for packet forwarding and reception. This is illustrated through analytical approach supported by computer simulations over mobile ad hoc wireless network containing 80 mobile nodes. The results showed that power savings of 50% were achieved with no delay in the network and increased throughput performance by 60%, as compared to a network with conventional ad hoc on‐demand distance vector and dynamic source routing protocols.